(untitled) (Journal of Hama University, 2019)
Cancer is the second leading cause of death after heart disease worldwide. More than 102 million Americans are diagnosed with cancer each year, affecting one or more of the body’s various sites, causing more than 550,000 deaths, especially lung, prostate, colon and rectum cancer. In men, colon and breast In women. The treatment of pain and its physical and psychological effects are important factors in the treatment plans for cancer, and of course vary types of pain and vary in severity and causes, and perhaps the most important causes of the effects and complications of cancer and various treatments, the application of massage from the things applied since ancient times and and can be defined as "a series of exercises carried out by the therapist and applied to the human body with preventive, health, therapeutic, rehabilitative and psychological objectives in a systematic and exemplary manner" consisting of basic maneuvers Including gentle massage, friction, disc and vibration. Studies indicate that the pain sensation of palliative care patients decreases after the application of the massage to children with cancer and chemotherapy after 18 hours .The study aimed to assess the effect of applying the massage technique using olive oil Pain in children with acute lymphatic leukemia in the department of chemotherapy in Tishreen Hospital in the city of Lattakia The study included two types of massage for the members of the sample are back massage and hand massage and the level of pain was measured before and after the application of the massage across the Visual Analogue Scale of pain (VAS). The results of the study showed statistically significant differences (P <0.005) in the low level of pain in the sample after the application of the hand and back massage.